Bahasa Indonesi - Jusniar Jusniar; Syamsidah; Army Auliah (Jurnal Penelitian Pendidikan IPA, 2023)
Green Chemistry (GC) is an issue that is very relevant to chemistry subjects in senior high schools. Chemistry subject is closely related to the environment as one of the pillars of sustainable development. This certainly contributes to the possibility integration of green chemistry principles into chemistry learning. This exploratory research aims to describe the principles of GC that allow it to be integrated into chemistry learning in grades X and XI; describes the high school teacher's and students' perceptions and understanding of GC and its principles in chemistryÂ  learning. The subjects in this study were 230 students who were selected purposively from five Senior high schools. Totally 40 chemistry teachers were purposively used as research subjects from a number of high schools throughout South Sulawesi. The instrument used was ten items of teacher's perception questionnaires, while the students' perception questionnaire consisted of twelve items. Guidelines for interviewing teachers and students were used to describe more deeply about their understanding of GC. All instruments have been validated by two experts. The results of the exploration of material elements for phases E and F show that five GC principles can be integrated into learning chemistry. In general, the teacher's perception of GC is good, which assumes that GC is an environmentally friendly concept. Understanding of the five principles of GC for students and teachers is in the moderate and poor categories. This shows the importance of integrating GC principles in the form of positive habits in chemistry learning.